From sugar binders to diabetes fighters: the lectin saga of antihyperglycemic activity through systematic review and meta-analysis - Simha N., Akshaya; Patil, Shashank M.; M. K., Jayanthi; N., Chaitra; Wong, Ling Shing; Kijsomporn, Jureerat; Raj, Ranjith; Ramu, Ramith (Frontiers in Pharmacology, 2024)
Lectins are carbohydrate-binding proteins that are extremely selective for sugar groups present in the other molecules. As a result, they perform a variety of roles in biological processes involving cell, carbohydrate, and protein recognition at the cellular and molecular levels. Since lectins can bind to carbohydrates, they may play a role in determining its rate of digestion. They also bind to some of the proteins that are involved in diabetes mellitus (DM) pathophysiology. The present review aims to summarize the efficiency of lectins from different sources as potential antihyperglycemic agents. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were employed for the drafting. In this regard, published scientific articles on the effects of different lectins on blood glucose (BG), glucose tolerance, hormonal effects, carbohydrate digesting enzymes, oxidative stress, and insulin production process were collected from reputed journals using electronic databases. Also, the toxicity effects of lectins from different sources were collected. A specific keyword search was completed to collect numerous articles with unique experimental designs and significant results. This was followed by selection of the requisite articles based on the criteria designed by the authors. Data extraction was based on the common research elements included in the articles. From 13 identified studies, 11 studies were considered after double screening based on the inclusion criteria. Further, all 11 pharmacological investigations were considered for review.Subsequent studies reflected on the pharmacological properties of lectins on BG level, oxidative stress, β-cell proliferation, insulin resistance, inhibition of carbohydrate digesting enzymes, body weight, food and water intake, lipid profile and other parameters. This review highlights lectins as potential anti-diabetic agents. However, due to a limited research, systematic evaluation is recommended for their development and promotion as effective potential anti-diabetic agents. The clinical efficacy and safety of lectins against diabetes mellitus must also be evaluated.